Laparoscopic Management of Giant Ovarian Cysts Using the Alexis Laparoscopic System®: A Case Series - Dubuisson, Jean; Heersche, Sidney; Petignat, Patrick; Undurraga, Manuela (Frontiers in Surgery, 2020)
Objective The aim of this study was to review the characteristics of patients who underwent laparoscopic removal of giant ovarian cysts using the Alexis Laparoscopic System® and confirm the safety and feasibility of this technique. Method We conducted a retrospective review of data of women undergoing the procedure from March 2014 to February 2019. Inclusion criteria were ovarian cysts of at least 15cm. Exclusion criteria were the presence of solid components and suspicion of neoplasia on imaging. Results Six patients were included in the series. Median size of the cysts at imaging was 22.8 cm (range 15 – 30 cm), while median volume was 5.9L (range 1.9 to 15.6L). Mean age of operated women was 59 years (range 21 to 88 years). All patients underwent exclusive laparoscopic management except one patient who underwent a conversion into midline laparotomy. The size of the skin incision initially performed to puncture the cyst ranged from 2.5 to 4cm. On final pathological reports, two cysts were mucinous cystadenomas, and four were serous cystadenomas. There was no epithelial ovarian cancer or borderline tumor in any of the specimen operated. Conclusion Laparoscopic management of giant ovarian cysts using the Alexis Laparoscopic System® is safe and feasible in well-selected cases. Midline laparotomy can thus be avoided, decreasing the risk of post-operative complications and increasing quality of life of patients.